“Elastic stretch cavity building” system in endoscopic thyroidectomy via the axillary approach: a case series - Chen, Gaoxiang; Ji, Xiaochun; Zhang, Hai; Luo, Yong; Wu, Weizhu; Teng, Weifeng; Zhang, Jianan; Zhou, Shaocheng (Frontiers in Oncology, 2023)
Background: Patients undergoing conventional endoscopic thyroidectomy via the axillary approach, which is commonly used clinically, suffered from a range of postoperative complications. This study aimed to prevent postoperative complications and evaluate patients’ satisfaction with cosmetic outcomes in endoscopic thyroidectomy via the axillary with the use of “Elastic Stretch Cavity Building” System. Methods: In this retrospective case series study, the clinical data of patients who were admitted to the Thyroid Surgery Department of Ningbo Medical Centre Lihuili Hospital between December 2020 and December 2021 for endoscopic thyroidectomy via the axillary approach under the “Elastic Stretch Cavity Building” System. Results: A total of 67 patients were included, all surgeries were successfully completed. The operation time was 75.61±13.67 minutes; the postoperative drainage volume was 109.97±37.54 ml; the average postoperative hospital stay was 4 (2-6) days. There was no skin ecchymosis, effusion or infection, hypocalcemia, convulsions, upper extremity dyskinesia, and temporary hoarseness after the surgery. The patients were satisfied with the cosmetic effects, and the cosmetic score was 4 (3-4). Conclusion: The “Elastic Stretch Cavity Building” System in endoscopic thyroid surgery via the axillary approach might reduce the risks of complications and achieve satisfactory results with the cosmetic outcomes.